X-ray structure of two Schiff bases: TURN-ON sensing of Fe3+ and Al3+ in the HepG2 cell line. Issue 45 (5th November 2020) - Dey, Sunanda; Maity, Suvendu; Purkait, Rakesh; Pal, Kunal; Ghosh, Prasanta; Jana, Kuladip; Sinha, Chittaranjan
Abstract : Two single-crystal X-ray characterized Schiff bases (HL′ and H2 L′′ ) are prepared to sense Fe 3+ and Al 3+ ions, respectively, in aqueous media. Abstract : The efficiency of the fluorescence sensitivity of a sensor may be tuned by the modulation of the steric and electronic parameters in the structure. In this study, the thiophenyl Schiff base ( E )- N 1 -(phenyl(pyridin-2-yl)methyl)- N 2 -(thiophen-2-ylmethylene)benzene-1, 2-diamine (HL′ ) exhibited very high selectivity and a sensitive fluorescence enhancement towards Fe 3+ with violet emission ( λ em, 385 nm; LOD, 3.8 nM). On the other hand, the naphthyl Schiff base ( E )-1-(((2-((phenyl(pyridin-2-yl)methyl)amino)phenyl)imino)methyl)naphthalen-2-ol (H2 L′′ ) exhibited fluorescence sensitivity towards Al 3+, showing blue emission ( λ em, 502 nm; LOD, 3.3 nM) in H2 O (HEPES buffer, pH 7.4) medium. The emission enhancement of HL′ upon binding to Fe 3+ may be considered to be due to the restriction of intramolecular rotation, while the selectivity of H2 L′′ towards Al 3+ may be due to the turn on emission through the restriction of excited state intramolecular proton transfer (ESIPT) and the introduction of chelation enhanced fluorescence (CHEF). Furthermore, DFT computation supported the sensing strategy and the probes were applied for intracellular detection of Fe 3+ and Al 3+ in HepG2 cell lines.